IMPLEMENTING COLLABORATIVE STRATEGIC READING (CSR) IN TEACHING READING: AN ACTION RESEARCH - I Gede Ludira Putra; Ni Wayan Krismayani; Anak Agung Putu Arsana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2023)
Reading comprehension is the act of understanding and comprehending the text. The readers need to understand and find the meaning of the text. This study was conducted to determine whether Collaborative Strategic Reading could improve the reading comprehension of eighth-grade students at SMPN 2 Denpasar. The subjects of this study were the eighth-grade students of SMPN 2 Denpasar, consisting of 41 students. Classroom action research is used in this study, which consists of two cycles with two sessions; each cycle consists of initial reflection, planning, action, observation, and reflection. The result of the study shows that the mean score for pre-test was 65.75; post-test I was 74.87; and post-test II was 78.41. The researchers also distributed a questionnaire to the students, and the result showed a positive response from the students about implementing Collaborative Strategic Reading. It can be concluded that a collaborative strategy could improve reading comprehension.